Effects of fulvic acid addition on laying performance, biochemical indices, and gut microbiota of aged hens - Xiao, Gengsheng; Liu, Shun; Yan, Xia; Yang, Yang; Qi, Qien; Feng, Xin; Gong, Li; Zhang, Huihua (Frontiers in Veterinary Science, 2022)
The purpose of this study was to appraise the effect of fulvic acid on production, biochemical indices, and gut microbiota of laying hens. A total of 252 Dawu Golden Phoenix laying hens (55-week-old) were allotted to two treatments randomly, each with six replicates and 21 hens per replicate, including the control group (CG) and fulvic acid (500 mg/kg) group (FA). The trial period was 8 weeks. Adding FA raised egg weight (P = 0.03), shell-breaking strength (P = 0.03), and reduced egg breaking rate (P < 0.01), compared with CG. There was no difference in eggshell thickness and egg shape index between the two treatments; however, the FA group increased egg production by 1.45% and reduced the feed-to-egg ratio by 0.09. Moreover, dietary FA decreased the aspartate aminotransferase levels in serum (P = 0.04), and glutathione peroxidase and total antioxidant capacity were increased (P = 0.02 and 0.04, respectively). Despite this, the two groups had no differences in the alpha diversity indices (PD_whole trees, Shannon, Ace, Simpson, Chao1, and goods_coverage). Obviously, at the phylum level, the abundances of Firmicutes were improved (P < 0.01), Actinobacteriota (P < 0.01), and Proteobacteria (P < 0.01) were reduced by dietary FA. Supplementation with FA could improve the abundances of Megamonas (P < 0.01) and reduce Enterobacter (P < 0.01) at the genus level. To sum up, this study showed the addition of 500 mg/kg FA may boost production and egg quality and modulate the cecal microflora abundance and serum biochemical indices of laying hens.